2021
DOI: 10.1590/1808-057x202112990
|View full text |Cite
|
Sign up to set email alerts
|

Has it become more readable? Empirical evidence of key matters in independent audit reports,

Abstract: The aim of this study was to analyze the effect of the adoption of Brazilian Accounting Standard - Auditing Technique 701 (NBC TA 701, in its Portuguese initialism) over the readability of audit reports. The study fills a gap in the literature by obtaining empirical evidence regarding the effect of NBC TA 701 on the readability and comprehensibility of audit reports. The study is important for verifying whether the disclosure of key audit matters (KAMs) improves the ease of reading and understanding audit repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
2
0
4
Order By: Relevance
“…As Marques et al (2021) highlighted, NBC-TA 701 mandates auditors to report the matters they consider most relevant throughout their work. The disclosure of key audit matters (KAM) presents challenges while impacting the perception of independent auditors' accountability, as indicated by Brasel et al (2016) and Gimbar et al (2016).…”
Section: Relevance Of Key Audit Mattersmentioning
confidence: 99%
“…As Marques et al (2021) highlighted, NBC-TA 701 mandates auditors to report the matters they consider most relevant throughout their work. The disclosure of key audit matters (KAM) presents challenges while impacting the perception of independent auditors' accountability, as indicated by Brasel et al (2016) and Gimbar et al (2016).…”
Section: Relevance Of Key Audit Mattersmentioning
confidence: 99%
“…Em relação aos principais assuntos de auditoria, as pesquisas enfocam sobre a relevância informacional dos PAAs aos investidores (Alves Júnior & Galdi, 2020), a associação dos PAAs com o gerenciamento de resultados (Santos et al, 2020), a relação entre as características das empresas e os PAAs divulgados (Ferreira & Morais, 2020), a influência da divulgação dos PAAs na remuneração dos auditores (Colares et al, 2021), a divulgação dos PAAs e a legibilidade do relatório dos auditores (Marques et al, 2021), o conteúdo informacional dos PAA e sua utilidade nas previsões dos analistas (Vargas et al, 2022).…”
Section: Estudos Anteriores: Relatório Dos Auditores Independentes Au...unclassified
“…Apesar do avanço, é essencial que os esforços dos reguladores não cessem. Conforme Marques et al (2021), é importante um monitoramento forte e constante sobre o conteúdo divulgado nos relatórios de auditoria, para a adoção dos PAAs não ser apenas "proforma".…”
Section: Principais Assuntos De Auditoria E Parágrafos De êNfaseunclassified
“…Many studies have indicated that disclosure of key audit matters (KAMs) improves perceived value and data reliability only when the disclosures are made by the Big Four audit firms. On the other hand, they also found that listing KAMs draws investors' attention to new and broader information, which may distract them from the core information in the audit report (Marques, Pereira, Aquino, & Freitag, 2021;Moroney, Phang, & Xiao, 2021;Shakhatreh, Alsmadi, & Alkhataybeh, 2020).…”
Section: Key Audit Matters and Audit Qualitymentioning
confidence: 99%